Tanggung Jawab Orang Tua dalam Menumbuhkan Kerohanian Anak Berdasarkan Prinsip Alkitab - Yanto Paulus Hermanto; Raymond Sutanto; Rivosa; Nira Olyvia Purmanasari (Matheteuo: Religious Studies, 2021)
The responsibilities of parents are certainly the determining factors for a child to grow spiritually. For this reason, this study was conducted to determine the extent to which parents have responsibility for the spiritual growth of their children, so that their children do not continue to live in sin, but become children who win over the power of sin. The author takes a qualitative approach by collecting books and journals related to responsibilities of parents for the spiritual growth of their children which include methods, teachings and examples that should be carried out by parents in educating their children. In this study, it was found that responsibilities of parents should be carried out throughout their life and the roles and responsibilities to a certain extent. And if their responsibilities are carried out properly and according to the truth of God's word, it is hoped that their children will become spiritually mature children.